Investigation of the role of traffic police function in reducing geographical inequalities in mortality from road traffic accidents - Fatemeh Shahbazi (Archives of Trauma Research, 2018)
Background and Objectives: Road traffic accident (RTA) is one of the major public health problems. Inequality in this problem and its trend has not been yet investigated in Iran. A better understanding of different contributing factors to RTA like inequalities can be helpful to reduce the negative influence of road crashes. Hence, this study aimed at examining geographical inequality in mortality from RTAs over the previous decades. Materials and Methods: In this cross-sectional study, all people who died from RTAs from March 2006 to February 2015 were selected. The data were taken from Legal Medicine Organization in Iran. The Theil index was used to estimate geographical inequality in mortality from RTA. Data were then analyzed using the Stata software. Results: During the 10-year period of this study, 210,582 people in Iran died due to RTA. The mortality rate that caused by RTAs has decreased during the study. We found a larger reduction in a mortality rate in suburban RTAs. In spite of the reduction in RTAs death, geographical inequality increased during the 10-year study. Conclusions: The findings of this study indicate that there is a geographical inequality in mortality from RTAs in Iran. This implies that effective interventions in reducing the RTAs should be distributed equally among regions of the country. Further research can be performed to investigate the causes of this inequality.